The CinQASE Model: Design to Practice Individual & Collaborative Critical Thinking Skill in Learning - Hunaidah Hunaidah; Endang Susantin; Wasis Wasis (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study is a preliminary study in the process of developing the Collaborative in Questioning, Analyzing, Synthesizing and Evaluating (CinQASE) learning model in improving individual critical thinking skills (InCT) and collaborative critical thinking skills (CCT). Research methods in developing this model include needs analysis, literature review, and field survey in the form of descriptive analysis. The results show that this innovation can survive as a theoretical basis for developing the CinQASE learning model. This is the basis for continuous research related to the development of learning models for learning physics in schools. The syntax of the CINQASE learning model includes (1) Orientation problem, (2) Individual Work, (3) Collaborative Thinking Teamwork, (4) Discussion Class, (5) Evaluation and Feedback. The implications of the CinQASE learning model make it one of the learning models that can improve individual critical thinking skills (InCT) and collaborative critical thinking skills (CCT).